2007
DOI: 10.1177/0960327107083451
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation kinetics and genotoxicity in lymphocytes of smokers living in mexico city

Abstract: Genotoxicity caused by tobacco smoke was assessed in peripheral blood lymphocytes of smokers living in Mexico City by determining sister chromatid exchange (SCE), cell proliferation kinetics (CPK), replication index (RI) and mitotic index (MI). Nicotine levels, and its major metabolite cotinine, were also estimated in urine samples using gas-chromatography-mass spectrometry to quantify smoking intensity. The outcome of the analysis and the comparison of the 77-smoker group with a non-smoking control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…The increased frequencies of chromosomal aberrations and sister chromatid exchanges in radiation workers could indicate a cumulative effect of low level chronic exposure to ionizing radiation, pointing to the relevance of conducting cytogenetic analysis in addition to physical dosimetry in such cases (Cardoso et al, 2001). Although cytokinetic and cytostatic effects have been detected in heavy and moderate smokers (Calderón-Ezquerro et al, 2007), smoking habits may or may not affect the genotoxic effect of chronic radiation exposure (Maffei et al, 2002;Hadjidekova et al, 2003;Sari-Minodier et al, 2007).…”
Section: Relevance Of the Adaptive Responsementioning
confidence: 99%
“…The increased frequencies of chromosomal aberrations and sister chromatid exchanges in radiation workers could indicate a cumulative effect of low level chronic exposure to ionizing radiation, pointing to the relevance of conducting cytogenetic analysis in addition to physical dosimetry in such cases (Cardoso et al, 2001). Although cytokinetic and cytostatic effects have been detected in heavy and moderate smokers (Calderón-Ezquerro et al, 2007), smoking habits may or may not affect the genotoxic effect of chronic radiation exposure (Maffei et al, 2002;Hadjidekova et al, 2003;Sari-Minodier et al, 2007).…”
Section: Relevance Of the Adaptive Responsementioning
confidence: 99%
“…Moreover, in one study the MN frequency was reported to be significantly lower in the smoker group than in the controls [19]. However, several studies have indicated that individuals who smoke a larger number of cigarettes per day (≥30 cigarettes per day) have a significantly increased MN frequency [3,9,18,22].…”
Section: Introductionmentioning
confidence: 97%
“…Many studies have shown that there is an increase in MN frequency with age [3,[9][10][11][12][13][14][15][16][17][18][19], although others have not shown any correlation between MN frequency and age [16,18,20]. As for the role of gender, most studies have reported that MN frequency in females is higher than that in males [3,9,12,14,[16][17][18][19]21], whereas in others the gender had no effect [16,18,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism underlying cigarette smoke-induced cerebrovascular injury regarding to stroke remains unclear, cigarette constituents are known to activate reactive oxygen species (ROS) on DNA damage within the vascular wall, leading to premature vascular aging and endothelial dysfunction 3,5,6) . A direct causality in which exposure to cigarette smoke results in elevated levels of DNA aberrations in various human cell types, including fibroblasts, lymphocytes and endothelial cells has been shown in earlier reports 7,8) . Recently, accumulating evidence from cohort studies revealed that the increased risk of stroke is generally associated with smoking 9,10) .…”
Section: Introductionmentioning
confidence: 75%